Comparative Study on Fracture Resistance after Use of Bleaching Agents - Sudha Mattigatti, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: As a relatively new innovation, ACTIVA BIOActive Restorative boasts an improvement thanks to "rubberized" resin, according to its makers. The mechanical properties, aesthetic appeal, and long-term durability of resin-based composites are all possessed by these ionic composite resins. Aim: To comaprae & evaluate FR of I-OB after use of bleaching agents. Material & method: In our study 135 single rooted pre-molar tooth in extracted form were prepared by removing debribs which was followed by NaBO3•4H2O, CP & H2O2 solution. Result: All the 3 blecahing agents show no significant differnce between them. Conclusion: Bleaching chemicals showed significnat influence in FR.